2018
DOI: 10.1093/gigascience/giy074
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequencing and de novo genome assembly of Ammopiptanthus nanus, a desert shrub

Abstract: Background Ammopiptanthus nanus is a rare broad-leaved shrub that is found in the desert and arid regions of Central Asia. This plant species exhibits extremely high tolerance to drought and freezing and has been used in abiotic tolerance research in plants. As a relic of the tertiary period, A. nanus is of great significance to plant biogeographic research in the ancient Mediterranean region. Here, we report a draft genome assembly using the Pacific Biosciences (PacBio) platform and gene annotation for A. nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…To identify the chitinase genes in A. nanus, the genome sequence and annotation data were obtained from the A. nanus genome project [33]. The Hidden Markov Model (HMM) seed profile of the Glyco_hydro_18 (PF00704) and Glyco_hydro_19 (PF00182) was downloaded from the Pfam database [34], and chitinase genes in A. nanus were identified using HMMER3 (v. 3.0) software [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the chitinase genes in A. nanus, the genome sequence and annotation data were obtained from the A. nanus genome project [33]. The Hidden Markov Model (HMM) seed profile of the Glyco_hydro_18 (PF00704) and Glyco_hydro_19 (PF00182) was downloaded from the Pfam database [34], and chitinase genes in A. nanus were identified using HMMER3 (v. 3.0) software [35].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, high-throughput sequencing technology has provided a great deal of nucleic acid data for A. nanus [32], especially recently, the whole genome sequencing was completed using single-molecule sequencing [33], which makes it possible to identify chitinase family at the genome level. In the present study, the genome-wide identification of chitinase in A. nanus was conducted and expression profiling of the chitinase family under cold and osmotic stress was performed using quantitative real-time PCR (qRT-PCR).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequence data were obtained from the A. nanus genome project [32]. The hidden Markov model (HMM) model of the Apetala 2 (AP2) (PF00847) was downloaded from the Pfam database [49], and the AP2/ERF family TFs in A. nanus were identified using HMMER3 (v. 3.0) software [50] with a defined threshold of E < 1e −5 .…”
Section: Identification Of Putative Ap2/erf Transcription Factors In mentioning
confidence: 99%
“…These studies have enabled the cloning, characterisation and validation of candidate genes shown as beneficial in other model study systems, conferring salinity and heat tolerance to Escherichia coli by the A. nanus betaine aldehyde dehydrogenase gene (Yu et al 2014), or cold tolerance by the A. nanus antifreeze gene AnAFP to both E. coli and tobacco (Deng et al 2014), among many others. Recently, the A. nanus genome was sequenced on the PacBio platform (Table 1; Gao et al 2018), providing an essential resource for functional genomics and improvement studies, with Ammopiptanthus fast becoming a model for understanding drought and cold tolerance.…”
Section: Securing the Future Of Legume Germplasm Diversitymentioning
confidence: 99%